Understanding the perception of deejays towards teaching Arabic for media purposes: A case study of IIUM.FM - Ahmad, Nor Zahidah; Mohd, Khariun Nisaa; El-Tingari, Salih (2016)
The evolution of teaching language for specific purposes has led to the growing of its needs in various fields and areas for different targeted individuals and groups. This study is conducted to explore the perceptions of Arabic-speaking deejays in learning Arabic for media purposes as well as to investigate their opinions and suggestions on Arabic language programme for media purposes. The current study employed a case study method to present the data which were collected using semi-structured interview. It was conducted with four female deejays from IIUM.FM channel who are also the students at International Islamic University Malaysia (IIUM). The obtained data were reported descriptively, aiming to discover the students’ attitudes and personal views on Arabic language for radio broadcasting. The main findings of the study revealed that there is lack of practices and trainings with respect to radio broadcasting in Arabic language. It is also reported that the speaking skill should be given priority over other languages in this field. Hence, the findings from this study will further contribute to the foreign languages teaching framework and at the same time to meet the general needs of Arabic language among the radio broadcasters in Malaysia.